A rare case of systemic lupus erythromatosus with acalculous cholecystitis as its first presenting feature - Patel, Shivani A.; Kumar, Karan R. (International Journal of Advances in Medicine, 2017)
SLE is an autoimmune disease of multisystem involvement primarily involving skin, kidney and joints. GI involvement is not a common feature of SLE, though acalculous cholecystitis (AAC) has been reported in patient with SLE. Most of the previous cases of AAC (with SLE) reported had occurred in diagnosed cases of SLE. We are hereby reporting a case of AAC diagnosed simultaneously with SLE. The patient responded to treatment with immunosuppresion with cyclophospamide.